Предмет:
МатематикаАвтор:
анонимПрименим формулы сложения:
sin3a = sin(2a + a) = sin2a * cosa + cos2a * sina.
cos3a = cos(2a + a) = cos2a * cosa - sin2a * sina.
Получим разность:
(sin2a * cosa + cos2a * sina)sina - (cos2a * cosa - sin2a * sina)/cosa.
Приведем к общему знаменателю.
(sin2a * cos2a + cos2a * sina * cosa - cos2a * sina * cosa + sin2a * sin2a)/(sina * cosa).
Упростим sin2a * (cos2a + sin2a)/(sina * cosa) = 2 * sina * cosa/(sina * cosa) = 2.
Использовали формулы sin2a = 2 * sina * cosa и cos2a + sin2a = 1.
Ответ: 2.
Автор:
helen97Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть